PEREMPUAN KORBAN PERDAGANGAN MANUSIA DI MADURA - Iskandar Dzulkarnain (Karsa: Journal of Social and Islamic Culture, 2015)
The study views the problematic of human trafficking in depth, that becomes a crucial issue in politic domain since 1990’s. Feminists, human right organizations, women social movements, and all thes sides that care about the issue are on attempts to reveal human trafficking, women who are immigrated forcedly and prostituted. This is an international problem and type of modern day slavery. By this point the researcher tends to describe women, the victims of human traficcking in Madura. The study uses biographic qualitative method resulting the description of the process of human trafficking genesis, victim period, and post victim period when they get back home. Economy, family endorsement, education, and self motivation have been the reasons of the human trafficking. The early process, placing, and returning cannot be seperated with the various kinds of sorrows—sexual harassment, raping, unsalaried, tortured, and longer woring hours. What a very long and sad biography. The researh result is hopefullyable  to attract the intentions of those who care against the human trafficking in order to act,  prevent, and to avoid cheated women in future.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i1.608